(untitled) (Journal of Engineering, 2006)
The aim of this research was to apply a numerical model capable of describing the thermal pollution in rivers. For this purpose a two-dimensional numerical model was applied for estimating temperature distribution in a river Momentum Conservation Equation and Thermal Energy Equation were used to describe the fdistribution and diffusion of temperature along the river subjected to thermal pollution point source. Furthermore the model incorporates the (k-e) turbulence model to calculate the distribution of turbulent viscosity The pressure distribution was determined using hydrostatic pressure equation. The partial differential equations were formalized and simplified to be solved using Alternative direction implicit- explicit method (ADI) with upwinding technique. The resulting system of linear simultaneous equations were then solved using Gauss-Elimination method. A laboratory physical model was built to find experimental data. These data were used for model verification with data obtained from Al-Daura power station and Tigris river. The model was found to be sensitive to the variation of river velocity and density difference and the model was found to be insensitive to the wind speed. The comparison of observed results from Al- Daura power station and laboratory physical model with those computed by the numerical model show a good agreement. The maximum absolute difference percentage are (16.2%, 8.6%) respectively